Escola Nova na “Página de Educação” (1930-1933): navegando nas palavras de Cecília Meireles no “Diário de Notícias” - Silva, Mariana Batista do Nascimento (2015)
This thesis falls within the field of History of Education and takes the New Cultural History as its theoretical reference. It aims to understand how Cecília Meireles represents the Progressive Education in her chronicles “Página de Educação” published in the newspaper Diário de Notícia from June 1930 to January 1933, considering that literary genre as a memory space, according to Pierre Nora. It also deals with a series of reports known as “Percorrendo as escolas do Distrito Federal” (“Visiting Federal District schools”) and published between November and December 1932 in which Meireles wrote about the situation and practices of 29 schools in the city of Rio de Janeiro. Only the chronicles concerning the Progressive Education and its key elements were chosen from approximately 800 “Páginas”. It focuses primarily the teacher (training, teaching, identity and so on) and the school (building, educative practices, function and so on). This thesis, therefore, intends to outline the ideas of Progressive Education held by Cecília Meireles as editor, journalist and writer of “Página de Educação”, which she turned into a battlefield in favour of that pedagogic movement. It uses the key concepts of the Education Historiography related to Proust, Le Goff, Ginzburg and mostly Chartier.